Development of control device for digital permanent equipment capable of temperature control in each rod - MoKim, Yong (International Journal of Engineering and Technology, 2018)
Background/Objectives: Digital permanent equipment is one of essential beauty treatment devices in beauty parlors. About 30 thousand of beauty parlors have been launching a startup every year. Needs of diverse hair style by a wide range of customers have become increasing and importance of digital permanent equipment is also increased.Methods/Statistical analysis: Digital permanent equipment is possible to control temperature at each rod. Reliability of parts which is used in circuit and product certification is so important that evaluation of reliability as well as product certification is implemented.Findings: Control devices such as power supply for rod, temperature setting for rod, and distribution module to control temperature in each module which generates control signal of heater and sensor in rod are developed not only to improve the convenience of permanent work that is controlled rod temperature by group unlike conventional products but also to allow with checking fault signal of each rod by an over current. Degree of precision for temperature control has greatly increased to utilize temperature sensor.Improvements/Applications: Prototype of digital permanent equipment which is able to control temperature of each rod is developed. Plans for reducing costs and increasing capacity through not only modularity of all circuitsbut development of control board with stability-guaranteed is implemented in this study.Â Â